Insect diversity in post-mining areas: Investigating their potential role as bioindicator of reclamation success - DAMAYANTI BUCHORI; AKHMAD RIZALI; GILANG ADITYA RAHAYU; IRDIKA MANSUR (Society for Indonesian Biodiversity, 2018)
Buchori D, Rizali A, Rahayu GA, Mansur I. 2018. Insect diversity in post-mining areas: Investigating their potential role as bioindicator of reclamation success. Biodiversitas 19: 1696-1702. Reclamation can be a pivotal process to return an ecosystem to its condition prior to human disturbance, by recreating a landscape so that its structure and function closely resemble a natural community. Unfortunately, there is a lack of empirical data as to whether reclamation efforts successfully establish sustainable of the ecosystem or not. The objective of this research was to study insect diversity in post-mining areas and investigate their potential role as bioindicators of reclamation success. An ecological research was conducted in post-mining reclamation areas managed by PT. Berau Coal in Binungan, East Kalimantan. We selected sub-areas that had been subject to reclamation efforts for varying periods, ranging from 2 to 10 years, for observation. We also used an area of undisturbed natural forest as a comparison. Inside each of these subareas of different reclamation age, insects were sampled using pitfall traps and malaise traps along a 100-meter transect. Our results showed that insect diversity differed in areas of different reclamation age. Based on CCA revealed that environmental factors i.e. pioneer tree age, vegetation diversity and soil chemistry (N total) affected the diversity of insects in the reclamation area. In particular, NMDS analysis showed different species composition in ant communities found in subareas of varying reclamation age. We conclude that ants are the most useful potential bioindicator to assess reclamation success in post-mining areas.